Penguatan Profil Pelajar Pancasila melalui Pembelajaran PPKn di Sekolah Dasar - Luvita Indah Pratiwi; Miftahul Hanifa; Nencya Safara; Chelsa Bunga Nagita; Salsabilla Dinar Sandhi (Universitas PGRI Madiun, 2026)
This study aims to analyze the role of Civic Education (PPKn) learning in strengthening the Pancasila Student Profile in elementary schools. The research employed a qualitative approach using a library research method by reviewing various scientific journals, books, and official policy documents related to the Merdeka Curriculum and the Pancasila Student Profile. Data were collected through documentation techniques and analyzed using content analysis. The findings indicate that Civic Education plays a strategic role in developing the six dimensions of the Pancasila Student Profile, namely faith and piety, global diversity, mutual cooperation, independence, critical thinking, and creativity. The implementation of student-centered learning models, such as Project-Based Learning, Problem-Based Learning, collaborative discussions, and contextual learning, contributes significantly to strengthening students' character. The success of implementing the Pancasila Student Profile is also influenced by teachers' competence, supportive school culture, and parental involvement. This study concludes that Civic Education serves as an effective medium for strengthening students' character and supports the successful implementation of the Merdeka Curriculum in elementary schools.